PENGARUH PENGALAMAN KERJA, INDEPENDENSI, OBJEKTIFITAS, INTEGRITAS, KOMPETENSI, DAN KOMITMEN ORGANISASI TERHADAP KUALITAS HASIL AUDIT. (STUDI PADA KANTOR AKUNTAN PUBLIK DI SEMARANG) - Metha Kartika Carolita; Shiddiq Nur Rahardjo (Diponegoro Journal of Accounting, 2012)
The purpose from this research is to analize factors that affect the quality of examination results of Public Accountant firm. This research is a continuation from Sukriah, et al. (2009) with the addition of variable by Ayu. (2009). This study was important to do because of the increasing of demand of financial statement’s users for qualified audit report. To collecting data in this research is using a purposive sampling technique. Data taken from Public Accountant firm in Semarang as respondent. In this research using a free variable (Independent) Job experience, Independency, Objectivity, Integrity, Competency, and Organizational Commitment have influence to quality of audit results. Techniques of data analysis done with descriptive statistical analysis, the classical assumption test, multiple linear regression analysis, and hypothesis testing with the aid of SPSS 16.0. The conclusion of this research is 4 variable like Job experience, Objectivity, Integrity and Organizational Commitment had positive effect on the quality of audit result. Otherwhile, Independency and Competency variable isn’t have a significant effect of quality of audit result.